The Effect of Trust, Product Quality, and Mobile Banking Services on Customer Satisfaction at Bank Syariah Indonesia Pekalongan Kajen - Astuti, Risma Novia Dwi; Awali, Husni (ZISWAF ASFA, 2023)
This research aims to determine the influence of the level of trust, product quality, and quality of mobile banking services on customer satisfaction at Bank Syariah Indonesia Pekalongan Kajen Branch. This research is quantitative research with sample data collection techniques based on field research on all customers who save and use m-banking at Bank Syariah Indonesia Pekalongan Kajen Branch. The sampling technique in this research used an accidental sampling technique based on the Lemeshow formula with a total sample size of 97 respondents. The data obtained from the questionnaire distribution was then processed with the help of the SPSS 26.0 program through research data instrument testing, classical assumption testing, regression testing, and hypothesis testing. This research shows that the variables of trust level, product quality, and mobile banking service quality significantly influence customer satisfaction at Bank Syariah Indonesia Pekalongan Kajen Branch, both simultaneously and partially.